The Viennese Grätzloase. The role of the commons in countering market-based transformations of the city. - Brait, Romana; Hammer, Katharina (TU Wien, 2017)
This paper focuses on an analysis of the "Grätzloase"program, which was launched by the Viennese city government in 2015. The program is supposed to create socially mixed shared spaces in the city and encourage citizens to participate in the shaping of public space. In our analysis of the Grätzloase program, we focus on the theory of the commons. The commons are debated as alternative ways of or - ganizing production and are defined by their specific social and institutional arrangement of production and utilization. We examine how commoning as a specific form of production can contribute to reshape public space. In our empirical analysis, we focus on whether and to what extent the Grätzloase program has transformed public space in Vienna. We examined its economic anatomy, the specific institutional arrangements and its cultural and social functioning. Furthermore, we focus on identifying the groups and elements that drive processes of inclusion and exclusion.
Keywords: Stadtsoziologie; Stadtraum; Öffentlicher Raum; Raumgestaltung; Partizipation; Transformation